2016
DOI: 10.1039/c6em00213g
|View full text |Cite
|
Sign up to set email alerts
|

Orthophosphate-P in the nutrient impacted River Taw and its catchment (SW England) between 1990 and 2013

Abstract: Excess dissolved phosphorus (as orthophosphate-P) contributes to reduced river water quality within Europe and elsewhere. This study reports results from analysis of a 23 year (1990-2013) water quality dataset for orthophosphate-P in the rural Taw catchment (SW England). Orthophosphate-P and river flow relationships and temporal variations in orthophosphate-P concentrations indicate the significant contribution of sewage (across the catchment) and industrial effluent (upper R. Taw) to orthophosphate-P concentr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 35 publications
1
5
0
Order By: Relevance
“…Therefore, it can be proposed that these step changes were brought about by the implementation of the UWWTD. This is in agreement with other studies from individual British rivers which have assessed changes in P concentrations, fluxes and eutrophication risk since the 1990s (e.g., Bowes et al 2010, 2011, Whitehead et al, 2013Earl et al, 2014;Bussi et a, 2016, Tappin et al, 2016. Worrall et al (2016) could show that urban land use was the important contributor to the explanation of TP flux across the UK but did not consider change in this urban source over time.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Therefore, it can be proposed that these step changes were brought about by the implementation of the UWWTD. This is in agreement with other studies from individual British rivers which have assessed changes in P concentrations, fluxes and eutrophication risk since the 1990s (e.g., Bowes et al 2010, 2011, Whitehead et al, 2013Earl et al, 2014;Bussi et a, 2016, Tappin et al, 2016. Worrall et al (2016) could show that urban land use was the important contributor to the explanation of TP flux across the UK but did not consider change in this urban source over time.…”
Section: Discussionsupporting
confidence: 91%
“…Muscutt and Withers (1996) carried out a study among 98 rivers in England and Wales and reported that 80% of the rivers were failing a target limit of of 0.1 mg/l mean orthophosphate concentration (DoE, 1993). However, the UK has increased investment and accelerated implementation of the UWWTD at STWs in the last decade (Bowes, et al, 2010): investment in England was almost doubled from £9600 M in the period 1990 -2000 to £16100 M in the years between 2000 -2015; with a total investment of £39126 M on STWs overall in the UK for the years between 1990(DEFRA, 2015. These actions have started to pay off with considerable reduction of phosphorus concentrations in many UK rivers (Kinniburgh & Barnett, 2010;Bowes, et al, 2009;Neal, et al, 2010c).…”
Section: Introductionmentioning
confidence: 99%
“…These authors used ordinary least squares regression (OLS) to quantify the relationship between load and flow, but in the current work the robust parametric bisquare weights linear regression was used because it is less sensitive to heteroscedastic data and the presence of outliers than OLS. 19,20 Concentration and flow data for all years for each site were used to estimate the slope value because the sampling frequency was generally only ca. 12 samples y -1 and alkalinity data were not available for all years.…”
Section: River Flow Greater Than Base Flowmentioning
confidence: 99%
“…These results corroborate that pollution favors gaseous flows in water bodies (Gonzalez-Valencia et al, 2014;Silva et al, 2016), by supporting the microbial community acting in these flows, and reinforce the concept that management measures, aiming at preventing or reducing anthropogenic impacts, should also be considered to mitigate CH 4 and CO 2 emissions from reservoirs (Ometto et al, 2013). Domestic sewage discharges are the likely impact on these reservoirs, according to the values of P-PO 4 3− , EC, DTC, TSS, and BOD, and should be prevented or at least minimized (Shiddamallayya and Pratima, 2008;Tappin et al, 2016;Vigiak et al, 2019;Coelho et al, 2020). Although not innovative, such observations in environmental samples reinforce the robustness of our data and strengthen the remainder conclusions drawn in this research.…”
Section: Limnological Factors Affecting Communities Correlated With Gaseous Flowsmentioning
confidence: 87%